Measuring Multidimensional Health Poverty in China - Chi, Xin-Xin; Liu, Xi-Hua; Zhang, Ze-Zhong (Frontiers in Public Health, 2022)
This paper defines the concept of "multidimensional health poverty," considering both the monetary aspects and multidimensional health deprivation of health poverty. Moreover, we set up the multidimensional health poverty index (MHPI) to measure health poverty in China by revising the traditional A-F MPI method, specifically, we use the CHE as a sufficient condition and income poverty as a necessary condition, as well as taking physical, mental and social health into account. The measurement result evidence that physical health, monetary dimensions (CHE and income poverty) and mental health contribute most to health poverty in China. In addition, the MHPI is significantly higher in rural areas than urban due to higher out-of-pocket medical payments and health deprivation in more dimensions. Compared with the traditional method, the MHPI is more accurate, stable, and comprehensive, making it more suitable for measuring health poverty.